RELOCATION OF ENTERPRISES AS A TOOL OF ECONOMIC SECURITY UNDER CONDITIONS OF MARTIAL LAW - Zelisko Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article studies relocation of enterprises as a tool of economic security under conditions of martial law. The main threats of the enterprises relocation in the conditions of war have been identified. It is determined that relocation is possible both within the country boundaries and abroad. It is found that today domestic enterprises have effective state support for relocation within the country, which is impossible when moving abroad. The research proves that significant advantages of relocation include physical preservation of the assets and capacities of the enterprise, restoration of its work and preservation of jobs. At the same time, in the course of the conducted research, the author identified a number of risks related with application of this tool, particularly, significant costs of relocation, impossibility to make adequate forecast of the costs spent in war conditions, restrictions on access to all types of resources, bureaucratic obstacles. Opportunities and risks of relocation have been studied for the enterprises continue their operation. The work identifies main problems and the geography of business relocation. Risks and threats to the country's economic system, regional economies, the domestic consumer market, business entities in conditions of the Russian-Ukrainian war have been assessed. Tools to support and mitigate threats of relocation of the enterprises are proposed. Implementation of the specified tools and means will allow to eliminate the outlined threats to the relocated business and minimize risks of the socio-economic development of the country. The main problems faced by domestic enterprises during relocation are analyzed. It is noted that there is the state support when relocating an enterprise within the country. Companies relocated abroad should radically revise their business strategies. When relocating abroad, it is important for the enterprises to study the peculiarities of running business in the chosen country, to estimate the financial costs associated with the relocation.